Genital ulcerative pyoderma gangrenosum in Behçet′s disease: A case report and review of the literature - Pinar Ozuguz; Seval Dogruk Kacar; Vildan Manav; Semsettin Karaca; Fatma Aktepe; Sena Ulu (Indian Journal of Dermatology, 2015)
Behçet′s disease (BD), first described by Hulusi Behcet, is a multisystemic disease characterized by recurrent oral and genital ulcerations, ocular and cutaneous lesions, arthritis and vascular disease. Pyoderma gangrenosum (PG) is a rare, chronic, sterile pustular and progressive ulcerative process of unknown cause; sometimes can participate in the differential diagnosis of Behcet′s ulceration. A 33-year-old woman complained a severe genital ulcer. She had a purulent oozing and stinky ulceration on the right side of labium minor measuring 5-8 cm. A punch biopsy at ulcer margin showed that the lymphocytic panniculitis was extending to the subcutaneous fat tissue without fibrin deposition or necrotic changes in the vessel wall. Based on the clinical and histological findings, she was diagnosed as genital ulcerative PG, which occurred during the exacerbation of BD.